Preparation of cast aluminium alloy-mica particle composites - Deonath; Bhat R.T.; Rohatgi P.K. (My University, 2025)
The optimum conditions for producing cast aluminium alloy-mica particle composites, by stirring mica particles (40 to 120 μm) in molten aluminium alloys (above their liquidus temperatures), followed by casting in permanent moulds, are described. Addition of magnesium either as pieces along with mica particles on the surface of the melts or as a previously added alloying element was found to be necessary to disperse appreciable quantities (1.5 to 2 wt.%) of mica particles in the melts and retain them as uniform dispersions in castings under the conditions of present investigation. These castings can be remelted and degassed with nitrogen at least once with the retention of about 80% mica particles in the castings. Electron probe micro-analysis of these cast composites showed that magnesium added to the surface of the melt along with mica has a tendency to segregate around the mica particles, apparently improving the dispersability for mica particles in liquid aluminium alloys. The mechanical properties of the aluminium alloy-mica particle composite decrease with an increase in mica content, however, even at 2.2% the composite has a tensile strength of 14.22 kg mm-2 with 1.1% elongation, a compression strength of 42.61 kg mm-2, and an impact strength of 0.30 kgm cm-2. The properties are adequate for certain bearing applications, and the aluminium-mica composite bearings were found to run under boundary lubrication, semi-dry and dry friction conditions whereas the matrix alloy (without mica) bearings seized or showed stick slip under the same conditions. © 1980 Chapman and Hall Ltd.